Penetration into bone and tissues of clindamycin phosphate. Issue 628 (February 1978) - Baird, P.; Hughes, S.; Sullivan, M.; Willmot, I.
Abstract : Clindamycin phosphate is an antibiotic which is effective against both Staphylococcus aureus and the anaerobic organisms. In thirteen patients, its concentration following joint replacement was measured by the agar diffusion method. In bone, the concentration was (mean +/- s.e. mean) 5.01 microgram/ml +/- 1.16, N=10; in capsule, 3.29 microgram/ml +/- 0.71, N=12; measured between 1.75 and 3.75 hr after intramuscular and intravenous injections, and in drainage fluid it amounted to 4.61 microgram/ml +/- 0.38, N=11 in 48 hr. Two patients developed diarrhoea which settled within a short period.